Impact of metabolic syndrome on the survival of Chinese patients with resectable esophageal squamous cell carcinoma. Issue 6 (1st September 2016) - Wen, Y.-S.; Huang, C.; Zhang, X.; Qin, R.; Lin, P.; Rong, T.; Zhang, L.-J.
Summary: Metabolic syndrome (MetS) is associated with the risk of esophageal squamous cell carcinoma (ESCC). However, the impact of MetS on survival has not been evaluated. A retrospective review was performed on 596 consecutive Chinese patients with esophageal squamous cell carcinoma who received surgery between January 2005 and October 2007. The clinical data and pretreatment information related to MetS were reviewed. The impact of MetS on overall survival (OS) was estimated by Kaplan–Meier and Cox proportional hazards analyses. MetS was a significant and independent predictor for better survival in patients with resectable ESCC. The 3-year OS and 5-year OS for patients with and without MetS were 75.0% versus 57.8% and 65.1% versus 44.6%, respectively ( P = 0.005 in the univariate analysis, P = 0.010 in multivariate analysis). However, there was no apparent influence of any single component of MetS on OS. The other independent prognostic factors identified in the univariate analysis included the following: gender, smoking status, alcohol use, the extent of radical surgical resection, T and N stage, and tumor differentiation. The results of the multivariate analysis included the extent of radical surgery resection, T and N stage, and tumor differentiation. MetS was also associated with greater tumor cell differentiation ( P = 0.036). There was no association found between MetS status and postoperative complications. MetS is an independent prognostic factor for OS in patients with ESCC and is associated with better tumor cell differentiation.